Enhancement of market opportunities for seaweed farmers: East Java in Indonesia - SRIWULANDARI, S.; MINTARTI WIDJAJA, S.U.; WAHYONO, H.; UTOMO, S.U. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to analyze factors causing seaweed farmers’ problems and examine the role of entrepreneurship in developing business. The research is descriptive. The subjects of the study were seaweed farmers from several countrysides in Sidoarjo, East Java. The findings indicated that increasing the sensitivity of farmers in capturing market opportunities could be boost through entrepreneurship. It can be conducted through the development of product innovations such as producing sticks, noodles, and crackers from seaweed. Furthermore, by involving technology, it can increase quality and competitive products. RESUMEN Este estudio tiene como objetivo analizar los factores que causan los problemas de los agricultores de algas. La investigación es descriptiva. Los sujetos del estudio fueron productores de algas de varios países en Sidoarjo, Java Oriental. Los resultados indicaron que aumentar la sensibilidad de los agricultores en la captura de oportunidades de mercado podría aumentar a través del emprendimiento. Se puede llevar a cabo mediante el desarrollo de innovaciones de productos, como la producción de palos, fideos y galletas de algas. Además, al involucrar tecnología, puede aumentar la calidad y los productos competitivos.